Psychology, environment and climate change: foregrounding justice (part two) - Barnes, Brendon R.; Barnwell, Garret; Hendricks, Lynn (PINS-Psychology in Society, 2022)
The world is experiencing unprecedented heating, extreme weather patterns, natural disasters, pollution, biodiversity loss, and environmental destruction with disproportionate impacts on marginalised peoples’ physical and mental health. Environmental and climate justice is increasingly used to frame research, practice and praxis. For example, activists on the margins are increasingly demanding that their voices are heard despite extreme levels of physical and epistemic violence. Countries in the global South are demanding reparations for the disproportionate harm caused by industrialised nations. For the first time, the latest IPCC report acknowledged the impacts of colonisation on climate change. However, much work needs to be done. With planetary health at a tipping point, it is crucial for all sectors and disciplines to urgently mobilise to acknowledge disproportionate impacts and reverse environmental degradation and climate change.